2021
DOI: 10.1002/lary.29525
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon‐performed Transoral Ultrasound‐Guided Aspiration of Peritonsillar Abscess

Abstract: View Video S1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The training or qualifications of the sonographers were not specified in 13 studies. The remaining five studies all described differing levels of training or qualification: (a) ultrasound credentialed at their hospital, 26 (b) met the ACEP emergency ultrasound training guidelines, 20 (c) a 30‐min didactic and hands‐on session, 21 (d) certification by the German Society of Ultrasound in Medicine, 30 and (e) formal training with >300 prior head and neck ultrasound scans 32 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The training or qualifications of the sonographers were not specified in 13 studies. The remaining five studies all described differing levels of training or qualification: (a) ultrasound credentialed at their hospital, 26 (b) met the ACEP emergency ultrasound training guidelines, 20 (c) a 30‐min didactic and hands‐on session, 21 (d) certification by the German Society of Ultrasound in Medicine, 30 and (e) formal training with >300 prior head and neck ultrasound scans 32 …”
Section: Resultsmentioning
confidence: 99%
“…formal training with >300 prior head and neck ultrasound scans. 32 Figure 2 summarizes the quality assessment using the QUADAS-2 tool. One study 23 was only published as a conference abstract and not as a full-text manuscript, so it could not be assessed using QUADAS-2.…”
Section: Re Sultsmentioning
confidence: 99%
“…With the development of small-footprint US transducers, the intraoral US technique has shown potential for oral tongue cancer detection and depth-of-invasion estimation [ 22 , 23 ]. For the oropharynx, a transoral US approach has shown improved visualization compared to transcervical US for the diagnosis of peritonsillar abscesses [ 24 , 25 ]. A small-sample feasibility study found that outpatient-performed transoral US had high sensitivity and specificity to differentiate oropharyngeal tumors from normal tissue, but the study was not performed blinded to histopathology for all included cases [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-frequency, small-footprint US transducers have recently been developed, resulting in increased superficial soft tissue resolution. We have previously described the use of transoral US for detecting peritonsillar abscesses [17,18]; however, the potential of high-frequency transoral US to diagnose OPCs has not been investigated in any prospective trials. Furthermore, since surgeon-performed neck US is increasingly used worldwide [19][20][21], we believe transoral US may be added to the outpatient clinical work-up.…”
Section: Introductionmentioning
confidence: 99%